Cyber Security Reacualization of Customer Data and Funds in The Optics of Electronic Information and Transactions - Kurrohman, Taufik; Wulandari, Fenny (Rechtsregel : Jurnal Ilmu Hukum, 2025)
The technological transformation in the digital era has changed the paradigm of the banking world. Financial access is now inseparable from space, distance, and time, as it only requires the internet and sophisticated devices for every customer to make transactions. On the other hand, cyber security of customer data and funds is very risky to be hacked with various instruments and methods such as fishing, spam, ransomware to cause material losses, historically cyber attacks have been experienced by Bank Indonesia on January 21, 2022, Bank BSI May 2023 and most recently Bank BRI on December 18, 2024, but not transparently impacting customers. Customer protection is based on the regulation of Law Number 1 of 2024 concerning Electronic Information and Transactions and does not specifically regulate the protection of customer data and funds. The purpose of the research focuses on the practical order of cyber regulation in protecting customer data and funds, and the reactualization of the provisions of laws and regulations. The research method was carried out with normative juridical analysis with qualitative normative data analysis. The results of the study show first, the actual condition of cyber security today through the provisions of the ITE law has not been carried out comprehensively verified in the context of law enforcement the evidentiary instruments are inadequate, the jurisdiction of the authority limits the accessibility of cyber security law enforcement, there has been no case of buying and selling bank customer data that has been punished in the second court, the reactualization of cyber security data and funds can be carried out by strengthening the evidentiary instruments for Law Enforcement, Interpol cooperation between countries specifically for cybersecurity.